Creating New Positions? Direct and Indirect Effects of a Subsidized Apprenticeship Program - Crépon, Bruno; Premand, Patrick (World Bank, Washington, DC, 2018)
Evaluations of employment programs usually focus on direct impacts on participants. Yet employment programs can have a range of indirect effects that are rarely quantified. This paper analyzes the impact of a subsidized apprenticeship program offering dual on-the-job and theoretical training in Côte d'Ivoire. The experiment simultaneously randomized whether apprenticeship positions opened by firms were filled by the program, and whether interested youths were assigned to a formal apprenticeship. This design allows for estimating direct impacts on youths and indirect impacts on firms selected to host apprentices. The analysis identifies whether individuals forgo other employment or training opportunities, and whether firms replace other workers with program participants. The share of youths in apprenticeships increased by 52.8 percentage points. This estimate accounts for a significant windfall effect: 26 percent of the formal apprentices who were placed substituted out of traditional apprenticeships. The inflow of apprentices into firms increased significantly, but also induced substitution effects, as firms hired 0.23 fewer traditional apprentices per formal apprentice placed. Overall, the net number of apprenticeship positions created was between 51 and 74 percent of the number of formal apprentices placed. In the short term, impacts on earnings were not significant for youths, but firms benefited from an increase in the net value of work provided by apprentices.